The Concept of Syafaq Abyaḍ in Determining the Beginning of the ʿIshāʾ Prayer Time - Ahmad Abrar; Friska Linia Sari (Astroislamica: Journal of Islamic Astronomy, 2026)
Prayer times are determined by the position of the Sun on the celestial sphere, including the Isha prayer, which begins with the disappearance of syafaq (twilight). Syafaq is classified into two types: syafaq aḥmar (red twilight) and syafaq abyaḍ (white twilight). The Shafi'i and Maliki madhhabs utilize syafaq aḥmar as their reference, whereas the Hanbali and Hanafi madhhabs rely on syafaq abyaḍ. In Indonesia, the Ministry of Religious Affairs (Kemenag RI) defines the start of Isha based on the disappearance of syafaq aḥmar at a solar altitude of -18°. However, light and air pollution significantly hinder the observation of this phenomenon. This qualitative field research aims to observe the disappearance of syafaq on Masalembu Island, an ideal location offering an unobstructed view of the western horizon and pristine, dark night skies (sky brightness value of 22.00 mag./arc sec²). Primary data were collected by recording night sky brightness using a Sky Quality Meter (SQM). The results indicate a discrepancy with the official regulations. While the Ministry of Religious Affairs establishes -18° as the threshold for the disappearance of syafaq aḥmar, field data reveal that even syafaq abyaḍ has completely vanished at this solar altitude. These findings emphasize the critical need for accurate twilight observations in pollution-free areas to ensure more precise determinations of Islamic prayer times.